MEMBANGUN BUDAYA ORGANISASI SEBAGAI UPAYA MENINGKATKAN DISIPLIN KERJA - Heni Rohaeni (Universitas Bina Sarana Informatika, 2010)
Organizational culture is a key value which is believed to also contain characteristics of the given member-Members of the organization to organization. Organizational culture is typically defined, with orientations along that unites existing personal or individual in the organization into a value system at different depth levels and gave him a different identity, so that the organization has a personality as a system of jointly accepted and will produce an effective organization, has a strong culture and different from other organizations. Beginning the process of formation of organizational culture, with the founding philosophy of the organization beginning with that create a certain selection criteria in determining the values and cultural norms. Furthermore, the subsequent acts or decisions and become the benchmark for members of the organization in determining behavior in organizations that are believed to be a cultural organization that is run by its members. Keyword: Organization culture, work discipline